2000
DOI: 10.1073/pnas.97.22.12260
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic progenitor cells grow on 3T3 fibroblast monolayers that overexpress growth arrest-specific gene-6 (GAS6)

Abstract: Pluripotential hematopoietic stem cells grow in close association with bone marrow stromal cells, which play a critical role in sustaining hematopoiesis in long-term bone marrow cultures. The mechanisms through which stromal cells act to support pluripotential hematopoietic stem cells are largely unknown. This study demonstrates that growth arrest-specific gene-6 (GAS6) plays an important role in this process. GAS6 is a ligand for the Axl (Ufo͞Ark), Sky (Dtk͞Tyro3͞Rse͞ Brt͞Tif), and Mer (Eyk) family of tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Chen et al (1997) have described interactions of the ligand Gas6 and the Mer/Axl/ Tyro-3 family of RTKs as being transforming in vitro (Chen et al, 1997) and Dirks et al (1999) have found these interactions to be associated with leukemia and lymphoma cell line proliferation. The Gas6-mediated stimulation of Mer that we observed in vitro should also occur with the Mer Tg lymphocytes in the bone marrow and peripheral blood in vivo, as Gas6 is produced by bone marrow stromal cells (Dormady et al, 2000) and is found in the plasma (Borgel et al, 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Chen et al (1997) have described interactions of the ligand Gas6 and the Mer/Axl/ Tyro-3 family of RTKs as being transforming in vitro (Chen et al, 1997) and Dirks et al (1999) have found these interactions to be associated with leukemia and lymphoma cell line proliferation. The Gas6-mediated stimulation of Mer that we observed in vitro should also occur with the Mer Tg lymphocytes in the bone marrow and peripheral blood in vivo, as Gas6 is produced by bone marrow stromal cells (Dormady et al, 2000) and is found in the plasma (Borgel et al, 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Subsequently, we added human IL-10 and hM-CSF function-blocking antibodies to the cocultures and found that the presence of both anti-hIL-10 and antihM-CSF attenuated mGas6 upregulation, whereas each antibody alone had no effect ( Figure 1H). Interestingly, this stroma-derived Gas6 was partially responsible for the well-known protective effect of BMDSCs on AML cells [34][35][36] because the pro-survival effect of S17 and OP9 cells on HL60 cells was reduced by sAxl, a Gas6-neutralizing "trap" molecule (supplemental Figure 1D). 37 In addition, we found that Gas6 contributed to the chemoprotective effect of BMDSCs on AML cells because sAxl decreased their pro-survival effect upon treatment with cytarabine ( Figure 1I).…”
Section: Cd38mentioning
confidence: 99%
“…X59846) attracted our special attention. As a secreted protein, GAS6 plays an important role in sustaining hematopoietic progenitor cells growth (25) and can induce mesangial cell proliferation (26). GAS6 could be involved in mediating the action of estrogen in mammary glands.…”
Section: Gas6 Is Induced By Estrogen In Normal Mammary Epithelial Celmentioning
confidence: 99%
“…Although amphiregulin is induced by estrogen and can stimulate the proliferation of mammary epithelial cells (27), mammary glands from the mouse model with amphiregulin null mutation can still respond to estrogen (28), indicating that there are other factors mediating the action of estrogen. Given the role of GAS6 in stimulating the proliferation of other cells (25,26) and its induction in mammary glands by estrogen, GAS6 could be one of the factors involved in the estrogen-stimulated ductal growth of mammary glands. Enhancement of GAS6 mRNA expression in normal mammary epithelial cells and ER positive breast cancer cells by estrogen.…”
Section: Gas6 Is a Direct Target Of Estrogen Receptormentioning
confidence: 99%